MENINGKATNYA HIDROGEN PEROKSIDA PADA VARIAN T16189C mtDNA SEMEN MANUSIA - Sudjarwo Sudjarwo (The East Java Biological Society, 2006)
Mitochondria are a site of cellular respiration through oxidative phosphorylation enzymatic reaction (OXPHOS), which is producing energy in the form of ATP (Adenosine Triphosphate). If abnormalities occur along cellular respiratory chain, ATP will decrease and Reactive Oxygen Species (ROS), will increase, one of which is hydrogen peroxide. ROS is an oxidation whose targets are lipid, protein and DNA, all of which may result in the decrease of spermatozoa motility. The detection of hydrogen peroxide was conducted by means of chemiluminescence using luminol, while the detection T16189C mtDNA variant was done using PCR-RFLP with restriction enzyme MnLI. In normozoospermia, hydrogen peroxide in 16189T was 4.4 ± 1.8 CPM/106 sp and in 16189C was 6.4 ± 1.8 CPM/106 sp. In asthenozoospermia, hydrogen peroxide in 16189T was 20.3 ± 8.3 CPM/106 sp while in 16189C was 62.5 ± 9.0 CPM/106 sp. Hydrogen peroxide in normozoospermia and asthenozoospermia 16189T and 16189C showed significant difference (p < 0.00; p < 0.01). In normozoospermia and asthenozoospermia, 16189T and 16189C has correlation with the decrease of motile spermatozoa motility (normozoospermia, p = 0.02; p < 0.05; asthenozoospermia p = 0.03; p < 0.05).